Add-on Pyridostigmine Enhances CD4+ T-Cell Recovery in HIV-1-Infected Immunological Non-Responders: A Proof-of-Concept Study - Valdés-Ferrer, Sergio I.; Crispín, José C.; Belaunzarán-Zamudio, Pablo F.; Rodríguez-Osorio, Carlos A.; Cacho-Díaz, Bernardo; Alcocer-Varela, Jorge; Cantú-Brito, Carlos; Sierra-Madero, Juan (Frontiers in Immunology, 2017)
Background: In human immunodeficiency virus (HIV)-infection, persistent T-cell activa-tion leads to rapid turnover and increased cell death, leading to immune exhaustion and increased susceptibility to opportunistic infections. Stimulation of the vagus nerve in-creases acetylcholine (ACh) release and modulates inflammation in chronic inflammato-ry conditions, a neural mechanism known as the cholinergic anti-inflammatory pathway (CAP). Pyridostigmine, an ACh-esterase inhibitor, increases the half-life of endogenous ACh, therefore mimicking the CAP. We have previously observed that pyridostigmine re-duces ex-vivo activation and proliferation of T-cells obtained from people living with HIV. Methods: We conducted a 16-week proof-of-concept open trial using pyridostigmine as add-on therapy in seven HIV-infected patients with discordant immune response receiv-ing combined antiretroviral therapy (cART), to determine whether pyridostigmine would promote an increase in total CD4+ T-cells. The trial was approved by the Institutional Re-search and Ethics Board and registered in ClinicalTrials.gov (NCT00518154). Results: Seven patients were enrolled after signing informed consent forms. We ob-served that addition of pyridostigmine induced a significant increase in total CD4+ T-cells (baseline=153.1±43.1 vs. week-12=211.9±61.1 cells/µL; p=0.02). Post-hoc analysis showed that in response to pyridostigmine, four patients (57%) significantly increased CD4+ T-cell counts (responders=257.8±26.6 vs. non-responders=150.6±18.0 cells/µL; p=0.002), and the effect persisted for at least one year after discontinuation of pyri-dostigmine. Conclusion: Our data indicates that in patients with HIV, add-on pyridostigmine results in a significant and persistent increase in circulating CD4+ T-cells.